Physical Education content alignment with physical literacy outcomes in early adulthood - Simonton, Kelly; Washburn, Nicholas; Fullerton, Sean; Garn, Alex (Journal of Health and Physical Literacy, 2022)
Purpose: Little is known about if and how the content taught in physical education (PE) influences physical literacy. This study examined alignment between the content young adults experienced in PE and that which they wished they had experienced (i.e., interest alignment), and that they think is important for health and wellbeing as adults (i.e., importance alignment). Further, we investigated the degree to which perceptions of content alignment predict indicators of physical literacy in adulthood including moderate-to-vigorous physical activity (MVPA), positive and negative PA attitudes, and physical self-concept. Methods: College students (N= 370) completed an electronic survey concerning PE content alignment, MVPA, PA attitudes, and physical self-concept. Results: Team sports and fitness activities were content experienced most often while personal and social responsibility activities, outdoor education, and fitness was content identified as most interesting and important. Interest alignment positively associated with MVPA and negatively with negative attitudes toward physical activity. Interest alignment and importance alignment were positively associated with physical self-concept. Conclusion: The content offered in PE appears to influence components of physical literacy in adulthood. As such, schools might consider revising curricula to include activities that create the foundation of an active lifestyle in adulthood.